Advantages and Disadvantages of Implementing a Regional Autonomy System on the Independence of a Region - Sivani Ardi Apritania; Ong Argo Victoria; Ratih Mega Puspa Sari (UNIVERSITAS PAKUAN, 2026)
The implementation of the regional autonomy system in Indonesia is a decentralization policy that aims to grant authority to regional governments to regulate and manage government affairs in accordance with the potential and needs of local communities. This policy is expected to improve the effectiveness of government administration, accelerate regional development, and realize regional independence in various aspects, including economic, social, and government administration. This study aims to analyze the advantages and disadvantages of the implementation of the regional autonomy system on the independence of a region by emphasizing the concepts of regional autonomy and regional independence, the benefits of implementing regional autonomy, and the challenges faced in its implementation. The research method used is normative legal research with a statutory and conceptual approach. Research data were obtained through literature studies covering primary legal materials, secondary legal materials, and tertiary legal materials, then analyzed qualitatively to gain a comprehensive understanding of the implementation of regional autonomy in Indonesia. The results of the study indicate that the implementation of the regional autonomy system provides various benefits for increasing regional independence. The authority held by regional governments allows for the formulation of policies that are more responsive to community needs, the development of local potential, improving the quality of public services, and optimizing the management of regional resources and revenues. In addition, regional autonomy encourages government innovation and strengthens community participation in the development process, thereby increasing regional competitiveness. However, the implementation of regional autonomy also faces a number of weaknesses and challenges, including capacity disparities between regions, limited human resources, fiscal dependence on the central government, overlapping regulations, and the potential for abuse of authority that can hinder the optimal realization of regional independence. This study concludes that the success of the regional autonomy system in realizing regional independence is greatly influenced by the quality of governance, institutional capacity, accountable financial management, and synergy between the central and regional governments. Therefore, strengthening regulations, improving the competence of apparatus, effective oversight, and community empowerment are needed so that the benefits of regional autonomy can be felt evenly and sustainably in supporting national development. Keywords: Autonomy; Decentralization; Independence; Regional.